The Role of the Shariah and Intangible Assets in Managing Cost of Debt and Enhancing Competitiveness across the Corporate Life Cycle - Diana Hasyim; Nurul Wardani Lubis; Ahmad Hidayat; Riza Indriani; Edison Parulian (Manunggal Halim Jaya, 2027)
This study investigates the multilevel relationship between normative values, asset based views, finance based views, and strategic management in Islamic economics. It aims to explain how intangible assets mediate the influence of the Shariah system on the cost of debt and competitiveness across corporate life cycle stages. Using panel data of 720 firm year observations from Shariah and non Shariah firms, the study applies a multilevel mediation–moderation model. The results show that investment efficiency partially mediates the relationship between the Shariah system and cost of debt through a suppressor effect, yielding a negative total effect. However, investment efficiency does not mediate the Shariah–competitiveness relationship. Conversely, corporate reputation partially mediates the link between the Shariah system and competitiveness, but not with the cost of debt. Furthermore, the moderating role of the corporate life cycle is nonlinear and dynamic, as the Shariah system’s ability to reduce cost of debt varies significantly from the introduction to the decline stage. These findings highlight the critical importance of life cycle perspectives in understanding cost efficiency and competitive strategy in Shariah compliant firms. Ultimately, this research provides vital implications for developing more adaptive Shariah based financial management policies.